Markowitz Portfolio Theory and Capital Asset Pricing Model for Kuala Lumpur Stock Exchange: A Case Revisited - Lee, Hui-Shan; Cheng, Fan-Fah; Chong, Shyue-Chuan (International Journal of Economics and Financial Issues, 2016)
Capital Asset Pricing Model is widely used by investors to estimate the return or the moving behavior of the stock and Markowitz Model is employed to achieve portfolio diversification. This study examine whether CAPM is valid to forecast the behaviour of the each individual stock and its return as well as its validity in the portfolio with stocks listed in Malaysia. Second, it evaluates the suitability of Markowitz Model to evaluate the performance of the Malaysia investment portfolio. This is done within the framework of 2010 to 2014 using weekly data of 60 companies. OLS unbiased estimator, autocorrelation and heterodasticity problems are to be conducted to test the validity of the model. It is concluded that CAPM is reasonable to be the indicator of stock prices in Malaysia as well as in portfolio basket. It proves that there is linearity in CAPM but unique risk and systematic do not need to be captured. Managers can use CAPM as a proxy to estimate their stock return and diversify the portfolio to reduce the unsystematic risk to enable them to execute the right policy in their management in order to maximise profit at the same time increase shareholder wealth maximisation. Furthermore, it is suggested to apply Markowitz portfolio diversification to reduce the unsystematic risk. Overall, portfolio diversification could build up the investors' confidence towards the investment decision and to develop a sound investment financial market in assisting Malaysia to achieve its mission to be a developed country in 2020. Keywords: Capital Asset Pricing Model, Risk and Return, Markowitz Portfolio Diversification JEL Classifications: G11, G12